2019
DOI: 10.1007/s13197-019-03749-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cacao bean quality grade on cacao quality evaluation by cut test and correlations with free amino acids and polyphenols profiles

Abstract: Cacao fermentation induces biochemical changes in the beans that lead to different cacao grades such as slaty (unfermented), violet (under fermented) and brown (fully fermented) beans. This grade heterogeneity in a sample set can impact the quality of the end-products. In the present study, amino acids and polyphenol contents of slaty, violet and brown beans were evaluated. Free amino acids were derivatized from o-phthalaldehyde and detected with a fluorescence spectrophotometer coupled with a reverse phase HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Also, presumably the fermentation environment used on cocoa bean influences the composition and content of the amino acids. The trend of change is different from the reports (Rohsius, Matissek, & Lieberei, 2006) (Tchouatcheu, Noah, Lieberei, & Niemenak, 2019). The differences in changes may be due to differences in process; Rohsius et al (2006) describes a comparative study on fermented (but not dried) cocoa beans.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…Also, presumably the fermentation environment used on cocoa bean influences the composition and content of the amino acids. The trend of change is different from the reports (Rohsius, Matissek, & Lieberei, 2006) (Tchouatcheu, Noah, Lieberei, & Niemenak, 2019). The differences in changes may be due to differences in process; Rohsius et al (2006) describes a comparative study on fermented (but not dried) cocoa beans.…”
Section: Resultscontrasting
confidence: 93%
“…A previous study showed a link between polyphenols and cocoa flavor intensity (Bariah, 2014). Polyphenols substance contents were significantly lower in under‐fermented and fully fermented beans when compared to raw beans (Tchouatcheu et al., 2019). The content of procyanidin was comparable to those (12.89%) of cocoa bean reported by Cienfuegos et al (Cienfuegos‐Jovellanos et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 a, the cocoa from Copallín registered a low content during almost the entire fermentation process. The FAA content was below the value mentioned by Tchouatcheu et al (2019) , where a fermented bean contained around 800 to 1400 mg/100 g; this may be because the study was performed in an aerobic process (with turnovers) ( Balcázar-Zumaeta, Pajuelo-Muñoz, et al, 2023 ), producing the oxidation of flavan-3-ols, which reacted with nucleophilic groups of amino acids to form insoluble complexes ( Schlüter et al, 2022 ), and the presence of microorganisms which limited the production of FAA content ( Rahardjo et al, 2022 ).
Fig.
…”
Section: Resultsmentioning
confidence: 90%
“…The cocoa quality and chocolate perception in flavor and aroma depend on the amino acid profile ( Dala-Paula, Deus, Tavano, & Gloria, 2021 ; Deus, Bispo, Franca, & Gloria, 2020 ). Moreover, a well-fermented cocoa bean presents a higher content of amino acids ( Tchouatcheu, Noah, Lieberei, & Niemenak, 2019 ); in addition, they are responsible for different physiological functions for humans ( Salaria, Boatwright, Thavarajah, Kumar, & Thavarajah, 2022 ), such as protein synthesis, repair tissues and nutrient absorption, among others ( Dala-Paula et al, 2021 ; Lopez & Mohiuddin, 2022 ). However, the concentration of amino acids varies by cacao origin, environmental conditions, and agricultural practices, among others ( de Araujo et al, 2021 ; Sari et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%